CHANGING CONDITIONS OF MAGMA ASCENT AND FRAGMENTATION DURING THE ETNA 122 BC BASALTIC PLINIAN ERUPTION: EVIDENCE FROM CLAST MICROTEXTURES - Sable J.E.; Houghton B.F.; Del Carlo P.; Coltelli M. (My University, 2006)
The Etna 122 BC basaltic eruption had two Plinian phases, each preceded and followed by weak phreatic and phreatomagmatic activity. This study infers changing eruption dynamics from density, grain size, and microtextural data from the erupted pyroclasts. The Plinian clasts show no evidence for quenching by external water; instead, all clasts are microvesicular and have high bubble number densities relative to the products of weaker basaltic explosive eruptions, suggesting that the 122 BC magma underwent coupled degassing linked to rapid ascent and decompression. This coupled degassing was probably enhanced by crystallization of abundant microlites, which increased the magma's effective viscosity during conduit ascent. Detailed measurements of vesicles and microlites show wide variations in number densities, size distributions, and shapes among clasts collected over narrow stratigraphic intervals. For such a diversity of clasts to be expelled together, portions of melt with contrasting ascent and degassing histories must have arrived at the fragmentation surface at essentially the same time. We suggest that a parabolic velocity profile across the conduit ensured that magma near the conduit walls ascended more slowly than magma along the axis, leading to a longer residence time and more advanced degrees of outgassing and crystallization in the marginal magma. In our model, accumulation of this outgassed, viscous magma along conduit walls reduced the effective radius of the shallow conduit and led to blockages that ended the Plinian phases. © 2006 Elsevier B.V. All rights reserved.
Keywords: BASALTIC PLINIAN; CONDUIT DYNAMICS; ETNA; MICROLITES; VESICLES